Serum Albumin and Globulin Levels in Pulmonary and Extrapulmonary Tuberculosis: A Cross-Sectional Study in Palembang - Pearly Laurencia; Subandrate Subandrate; Sadakata Sinulingga; Dwi Indira Setyorini (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Introduction. Alterations in serum albumin and globulin reflect inflammatory responses in tuberculosis (TB), but evidence linking them to TB type remains inconsistent. This study investigated the association between serum albumin, globulin, albumin/globulin (A/G) ratio, and TB type (pulmonary [PTB] vs. extrapulmonary [EPTB]) in adult patients at Dr. Mohammad Hoesin Hospital, Palembang. Methods. A cross-sectional study was conducted among adult TB patients with measured serum albumin and globulin levels. TB type was categorized as PTB or EPTB. Associations were analyzed using chi-square tests, and prevalence ratios (PR) were calculated to quantify the strength of associations. Results. Among 251 patients, low serum albumin was more frequent in EPTB (41.7%) than in PTB (28.4%) (p = 0.006; PR = 1.802; 95% CI: 1.178–2.757), indicating EPTB patients were 1.8 times more likely to have low albumin. No significant association was observed for globulin: high globulin occurred in 56.7% of EPTB vs. 52.9% low-to-normal in PTB (p = 0.323; PR = 1.471; 95% CI: 0.682–3.174). Similarly, the A/G ratio showed no significant difference: low A/G ratio in 50% of PTB vs. 42.1% of EPTB (p = 0.676; PR = 1.376; 95% CI: 0.641–2.954). Conclusion. Lower serum albumin is significantly associated with EPTB compared to PTB, whereas globulin and the A/G ratio are not. Albumin may have potential as a supplementary clinical indicator of inflammatory status and disease manifestation in TB, though further longitudinal studies are warranted.